1999
DOI: 10.1097/00002060-199905000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapy in the Management of Heterotopic Ossification of the Elbow

Abstract: Heterotopic ossification, or the appearance of ectopic bone in para-articular soft tissues after surgery, immobilization, or trauma, complicates the surgical and physiatric management of injured joints. The chief symptoms of heterotopic ossification are joint and muscle pain and a compromised range of motion. Current therapies for prevention or treatment of heterotopic ossification include surgery, physical therapy, radiation therapy, and medical management. Unlike heterotopic ossification of the hip, heteroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 23 publications
1
41
0
3
Order By: Relevance
“…Initial reports found indomethacin to be effective in preventing clinically important HO, which has been defined as Brooker Classes III and IV HO [4], although more recent prospective studies have found increased risk of posterior wall nonunion and no change in rates of clinically important HO [22]. Radiotherapy prevents abnormal formation of bone by inhibiting the differentiation of mesenchymal stem cells to osteogenic pathways [8,19]. Although radiotherapy has been shown to be effective in numerous studies, the potential risk of malignant transformation and wound complications must be considered [1,4,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports found indomethacin to be effective in preventing clinically important HO, which has been defined as Brooker Classes III and IV HO [4], although more recent prospective studies have found increased risk of posterior wall nonunion and no change in rates of clinically important HO [22]. Radiotherapy prevents abnormal formation of bone by inhibiting the differentiation of mesenchymal stem cells to osteogenic pathways [8,19]. Although radiotherapy has been shown to be effective in numerous studies, the potential risk of malignant transformation and wound complications must be considered [1,4,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, measures should be taken to prevent recurrence. In addition, pre-and postoperative medication and radiation are helpful in reducing the recurrence of the heterotopic bone [15].…”
Section: Discussionmentioning
confidence: 99%
“…They are purported to act through a combination of factors such as delaying apatite crystal aggregation, inhibiting calcium phosphate precipitation and reducing the conversion of calcium phosphate into hydroxyapatite (9). Previous studies (10,11) have shown that bisphosphonate therapy can slow the progression of HO and ultimately result in smaller lesions, although long-term outcomes were not documented.…”
Section: Discussionmentioning
confidence: 99%